2003
DOI: 10.4028/www.scientific.net/ssp.95-96.175
|View full text |Cite
|
Sign up to set email alerts
|

Metal Content of Multicrystalline Silicon for Solar Cells and its Impact on Minority Carrier Diffusion Length

Abstract: The metal content of three types of silicon material for cost-efficient solar cells, Astropower silicon-film sheet material, Baysix cast material, and EFG ribbon-grown multicrystalline silicon was determined using instrumental neutron activation analysis. Iron, nickel, and chromium were found in concentrations between 10 12 and 1.8´10 15 cm -3 , depending on the material. The concentration of cobalt, molybdenum, and copper was between 10 12 and 5´10 13 cm -3 . Since the minority carrier diffusion length in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 17 publications
1
38
0
2
Order By: Relevance
“…19 Multicrystalline silicon (mc-Si), the cost-effective material out of which an increasing 50% of solar cell modules are currently produced 20 , typically contains high transition metal concentrations combined with a high density and variety of structural defects. Not surprisingly, copper-rich particles have been observed at structural defects in poorly-performing regions of mc-Si solar cell material [21][22][23][24][25] , complementing neutron activation analysis (NAA) data reporting Cu concentrations in mc-Si as high as 10 13 cm -3 . 26 While Cu-rich clusters are undoubtedly not the only type of defect responsible for reducing the efficiencies of mc-Si solar cells, their known recombination activity and repeated observation in poorly-performing regions indicate they most certainly can be a contributing factor.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…19 Multicrystalline silicon (mc-Si), the cost-effective material out of which an increasing 50% of solar cell modules are currently produced 20 , typically contains high transition metal concentrations combined with a high density and variety of structural defects. Not surprisingly, copper-rich particles have been observed at structural defects in poorly-performing regions of mc-Si solar cell material [21][22][23][24][25] , complementing neutron activation analysis (NAA) data reporting Cu concentrations in mc-Si as high as 10 13 cm -3 . 26 While Cu-rich clusters are undoubtedly not the only type of defect responsible for reducing the efficiencies of mc-Si solar cells, their known recombination activity and repeated observation in poorly-performing regions indicate they most certainly can be a contributing factor.…”
Section: Introductionmentioning
confidence: 67%
“…Cu 3 Si clusters, or individual Cu atoms, may be stabilized either by the lattice strains of adjacent structural defects or other metal clusters. 21,70 Specifically, the chemical interactions between Cu and other metal species (of which mc-Si contains an abundance 24,26 ) are not well understood at the present time. The singular result of all these effects would likely be a somewhat lower effective segregation coefficient for mc-Si than that for singlecrystalline silicon.…”
Section: Al-gettering and Dissolution Of Cu Precipitatesmentioning
confidence: 97%
See 1 more Smart Citation
“…It is especially important in multicrystalline silicon wafers, in which it occurs primarily due to contamination from the crucible during ingot growth [1,2]. Typical concentrations of Fe in directionally-solidified multicrystalline ingots are 10 13 -10 14 cm -3 in the central regions, and up to 10 15 cm -3 near the bottom and top of the ingots [3,4], due to impurity segregation and solid-state indiffusion of Fe from the crucible walls.…”
Section: Properties Of Iron In Siliconmentioning
confidence: 99%
“…When metal impurities conglomerate to form large precipitates at grain boundaries and dislocations in Si wafers, the precipitated impurities usually have low recombination activity. In contrast, the recombination activity of the metal impurities would be high enough to reduce the minority carrier diffusion length to less than 1 μm if the impurities with high concentrations were in interstitial or substitutional sites [13][14][15]. It can be concluded that the properties of Si wafers and the resulting performance of solar cells not only depends on the total concentrations of impurities, but also on the structure, chemical state and spatial distribution of the impurities in the Si wafers.…”
Section: Influence On Electrical Propertiesmentioning
confidence: 99%